Effects of fear on donations to climate change mitigation - Palosaari Esa; Herne Kaisa; Lappalainen Olli; Hietanen Jari (Elsevier, 2025)
Despite 70 years of research, there is no consensus about the effects of threat messages on behavior, partly because of publication bias. The lack of consensus concerns situations such as climate change where people tend to believe that they cannot easily make a major difference. Using a 2 × 2, (threat, neutral) × (efficacy, no efficacy) between-subjects design, we tested four hypotheses: the effect of threat stimuli on (1) mitigation of climate change and (2) experienced fear depends on efficacy information, (3) threat stimuli increase monetary donations to mitigation regardless of efficacy information, and (4) the effect of the threat stimuli depends on political identity. The threat stimuli were climate change related pictures and a prompt to write either about one's knowledge of or about the threat of climate change. The efficacy stimuli were an efficacy related picture and written information about the efficacy of a climate change mitigating organization. We collected a representative online sample of 1517 U.S. citizens. The manipulations affected experienced fear and self-efficacy, but there was no statistically significant main effect of threat on donations nor a statistically significant interaction between threat and efficacy or between threat and political identity. It is concluded that threat appeals do not increase climate change mitigation behavior by more than a very small amount compared to making people think about the subject.